REJIM KEBIJAKAN DALAM DINAMIKA KEBIJAKAN PEMBANGUNAN KOTA - Nadir, Sakinah (JPP (Jurnal Politik Profetik), 2018)
This paper aims to show importance of the Urban Regime Theory in observing and analysing political dynamics in urban area development policies. Based on some research studies that done by some scholars, this paper shows fact that in context of the urban development policies, there is actor who playing very dominant roles more than others. Although there are various actors with different backgrounds and but the policy still dominate by the dominat actor. This actor is ultimately influences direction and inclination of a development policy in the urban area that is called as the Urban Regime.